Investigation of the Effects of Genistein and Fenretinide on Ovarian Cancer Cells - Azadi, Behnam (Université d'Ottawa / University of Ottawa, 2012)
The effects of the fenretinide and genistein as single or combined drugs on ovarian cancer proliferation and viability were investigated. Hypothesis: Co-treatment with genistein will enable a lower dose of fenretinide to be effective in inhibiting the proliferation and survival of ovarian cancer cells. Methods: Low and high doses of genistein and fenretinide were tested on A2780s and A2780cp cells using trypan blue viable cell count, MTS assay. Results and conclusions: Unlike low doses of fenretinide, genistein had anti-proliferative effects on both cell lines. There were no additive or synergistic effects of the two compounds. Higher dose treatments induced anti-proliferative effects and apoptotic cell death in both A2780s and A2780cp cells, with a greater sensitivity of A2780s cells to both test compounds. Overall Conclusion: Genistein and higher doses of fenretinide similarly impair cell cycle progression and induce apoptosis. The anti-proliferative effects of genistein can be affected by co-treatment with fenretinide
Keywords: Ein: Genistein; Fen: Fenretinide; SM: Soy Milk